Penerapan Model Edukasi Gizi terhadap Perilaku Sarapan pada Anak Sekolah Dasar - Jurianto Gambir; Nopriantini Nopriantini (Jurnal Vokasi Kesehatan, 2018)
Abstract: Application Of Nutrition Education Model To Breakfast Behavior In Basic School Children. Based on Data Riskesdas, (2010), 16-59% of school children in Indonesia are not accustomed to breakfast. School children who are used to breakfast 44.6% with energy consumption levels <15% AKG, 70% with poor breakfast nutritional quality with only drinking water / coffee / tea or with 1 (one) piece of small cake. Behavior is strongly influenced by various faktors including knowledge, intention and motivation of children to do breakfast, so needed a method to move child intention in doing breakfast. This research used to know how far effect of nutrition education to knowledge, habit, nutritional value and arrangement of breakfast food. The research method used was quasi experiment (Non-Randomized group pre-post test) with research subjects as many as 50 children divided into 2 (two) treatment groups (each group consists of 25 people). Educational media used the method of playing a smart ball game and counseling. The result of this research is there is a significant difference of knowledge level and value of knowledge score in both groups. The group of children who were educated with smart ball games had an average score higher than the group of children who received education through counseling (p <0.05).Abstrak: Penerapan Model Edukasi Gizi terhadap Perilaku Sarapan pada Anak Sekolah Dasar.  Data Riskesdas, (2010), 16-59% anak sekolah di Indonesia  tidak terbiasa  sarapan.  Anak sekolah yang terbiasa sarapan 44.6% dengan tingkat konsumsi energi <15% AKG, 70% dengan mutu gizi sarapan yang tergolong buruk dengan hanya minum air/kopi/teh atau dengan 1 (satu) potong kue kecil. Penelitian ini bertujuan mengetahui sejauh mana pengaruh edukasi gizi terhadap pengetahuan, kebiasaan, nilai gizi dan susunan makanan sarapan. Metode penelitian yang digunakan adalah quasi experiment (Non-Randomized grup pre–post test) dengan subyek penelitian sebanyak 50 anak dibagi dalam 2 (dua) kelompok perlakuan (masing kelompok terdiri dari 25 orang). Media edukasi yang digunakan penggunaan metode permainan bola pintar dan penyuluhan. Hasil Penelitian ini adalah ada perbedaan yang signifikan tingkat pengetahuan dan nilai skor pengetahuan pada kedua kelompok. Kelompok anak yang mendapatkan edukasi dengan permainan bola pintar memiliki rata-rata skor nilai lebih tinggi dibandingkan dengan kelompok anak yang mendapatkan edukasi melalui penyuluhan (p<0,05).